2013
DOI: 10.1177/0883073813476140
|View full text |Cite
|
Sign up to set email alerts
|

Can Children With Hyperlipidemia Receive Ketogenic Diet for Medication-Resistant Epilepsy?

Abstract: The very-high-fat ketogenic diet can worsen lipid levels in children with pre-existing hyperlipidemia by increasing serum lipoproteins and reducing antiatherogenic high-density lipoproteins. A retrospective chart review of 160 children treated with the ketogenic diet from September 2000 to May 2011 was performed. Twelve children with pre-existing hyperlipidemia were identified. Lipid levels including total cholesterol, low-density lipoprotein, triglycerides, high-density lipoprotein, and total cholesterol/high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Similar to our findings, many studies reported increased serum levels of total cholesterol, triglyceride, and LDL and decreased serum levels of high density lipoprotein in patients treated with KD (2,5,6,7,16). Whereas, in a single study investigating the effect of KD treatment on serum lipids in 66 healthy obese subjects with a body mass index greater than 30 kg/m 2 , the level of total cholesterol, LDL cholesterol, and triglyceride levels were found significantly decreased, whereas HDL cholesterol ievels significantly increased after the treatment in patients both with and without prior hypercholesterolemia (15).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 94%
“…Similar to our findings, many studies reported increased serum levels of total cholesterol, triglyceride, and LDL and decreased serum levels of high density lipoprotein in patients treated with KD (2,5,6,7,16). Whereas, in a single study investigating the effect of KD treatment on serum lipids in 66 healthy obese subjects with a body mass index greater than 30 kg/m 2 , the level of total cholesterol, LDL cholesterol, and triglyceride levels were found significantly decreased, whereas HDL cholesterol ievels significantly increased after the treatment in patients both with and without prior hypercholesterolemia (15).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 94%
“…Hyperlipidemia is a well-known side effect of almost all KDT. 137,[145][146][147][148] Increased serum triglycerides and total and low-density lipoprotein (LDL) cholesterol levels have been reported in 14-59% of children on the classic KD. 129,137,147,148 Hyperlipidemia can be seen as early as the first month of therapy.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…However, in one study, it was shown that despite the high dietary fat content of KD, serum levels can be controlled in children with hyperlipidemia prior to starting the classic KD. 146 Strategies to prevent KDinduced hyperlipidemia include increasing consumption of MCT and olive oil, supplementing with omega-3 fatty acid or carnitine while decreasing the intake of trans fat, saturated fat, and cholesterol; decreasing the KD ratio; and excluding all fatty meats, egg yolk, cream, butter, animal fat, palm oil and coconut oil; and using a solely formulabased KD. [146][147][148] Although the risk for coronary artery disease may increase with long-term elevations of cholesterol levels, previous pediatric studies showed no change in the carotid intima-media thickness compared to baseline at 6 and 12 months of therapy.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Although lipids have been shown to increase, these typically plateau over time and then decrease back to baseline . One study of 12 children with preexisting hyperlipidemia showed a significant reduction in cholesterol and low‐density lipoprotein, with 75% achieving normal values 12 months after classic KD initiation . Another study of adults on the MAD showed a significant increase in total cholesterol and low‐density lipoprotein over the first 3 months of treatment, but by 1 year these normalized and were not significantly different than baseline and remained stable for patients who remained on the diet for one or more years .…”
Section: Misconceptions About Ketogenic Dietary Treatmentmentioning
confidence: 99%